CONOPT – a package for solving nonlinear programming problems using a new (minimax) approach with efficient gradient methods - Bandler, John W.; Chen, J.H.K.; Jha, Virendra K. (Communications Research Laboratory, 1973)
CONOPT is a modified version of GRADMIN to be used for solving constrained optimization problems. A new technique proposed by Bandler and Charalambous is used to transform the constrained optimization problem into the minimization of an unconstrained objective function.
Program package produced by John W. Bandler, J.H.K. Chen, and Virendra K. Jha. This work is licensed under a Creative Commons Attribution-Non-Commercial-No-Derivatives 4.0 International License.
Keywords: optimization; nonlinear programming; minimax optimization